Determinação de Cl, I e Hg de forma direta em amostras diversas por espectrometria de absorção atômica e molecular de alta resolução com fonte contínua em forno de grafite - Guarda, Ananda Fagundes (2017)
Three analytical methods were developed for the determination of chlorine, iodine and mercury in solid and liquid samples, directly by high resolution continuum source atomic and molecular absorption spectrometry in graphite furnace. The first method objected the determination of chlorine in solid and slurry samples of different natures and chlorine contents (CRM 81002b human hair, SRM 1568b rice flour, ERM EC681 polyethylene, CRM BCR 460 coal, SRM 2692c bituminous coal, SRM 1575 sheet Of pine, CRM 686-1 iron oxide, SRM 1549 powdered milk) through the molecular formation of CaCl. The results were compared with those already available for the SrCl molecule and were superior, especially in samples with a high calcium content. The limit of detection and quantification obtained for the two molecular absorption lines of CaCl were 2.6 and 8.7 ng (620.862 nm) and 14.2 and 61.6 ng (377.501 nm), respectively. The iodine determination was performed through the formation of the SrI molecule in two samples of medicines containing iodine. The accuracy of the method was proved by comparative analysis by inductively coupled plasma mass spectrometry. The results obtained were higher compared to the existing BaI molecule that does not provide direct determination in solids. The limit of detection and quantification obtained were 0.035 and 0.117 μg, respectively. Finally, an analytical method for the determination of mercury in blood samples (SERONORM® LEVEL III and II) and urine (SERONORM®, Clincheck Control level I and II batch 432 and level II batch 923) were developed, directly, using gold nanoparticles. The method was compared to the existing method that uses potassium permanganate as oxidizing agent. The limit of detection and quantification obtained were 0.057 and 0.190 ng, respectively.